1975
DOI: 10.1084/jem.142.4.1023
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of T-lymphocyte-mediated tumor-specific lysis by alloantisera directed against the H-2 serological specificities of the tumor

Abstract: After appropriate in vivo or in vitro immunization, cytotoxic T lymphocytes (CTL) are generated which efficiently kill cells bearing particular membrane antigens in common with the immunizing cell (reviewed in reference 1). Such CTL have been most thoroughly studied in mice, employing alloimmunization with cells differing at the major histocompatibility locus, H-2. in such cases, the predominant cell surface antigens recognized by the CTL appear to be the molecules carrying the serologically defined H-2 specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
32
1

Year Published

1976
1976
1978
1978

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(36 citation statements)
references
References 10 publications
3
32
1
Order By: Relevance
“…The same phenomenon exists in the interaction between T-killer lymphocytes and syngeneic virusinduced tumor cells. This has been demonstrated both by immunization with oncogenic viruses (5)(6)(7)(8) and by grafl~ of syngeneic virus producer lymphoma cells (9)(10)(11). In murine sarcoma virus (MSV) tumors and in Friend virus (FLV) leukemias, such H-2 restrictions of CTL activity have been shown to occur during both primary in vivo response (5,6,9) and secondary in vitro CTL restimulation (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The same phenomenon exists in the interaction between T-killer lymphocytes and syngeneic virusinduced tumor cells. This has been demonstrated both by immunization with oncogenic viruses (5)(6)(7)(8) and by grafl~ of syngeneic virus producer lymphoma cells (9)(10)(11). In murine sarcoma virus (MSV) tumors and in Friend virus (FLV) leukemias, such H-2 restrictions of CTL activity have been shown to occur during both primary in vivo response (5,6,9) and secondary in vitro CTL restimulation (12).…”
mentioning
confidence: 99%
“…Though the exact role of H-2 directed molecules in the anti-MSV and anti-FLV reactions by syngeneic CTL is unknown, the hypothesis that the reactions are directed against altered self specificities as in other systems (1-4) appears more probable than the one requiring a double contact and sometimes designated as the intimacy theory (5,9,10,13). In most systems both Ho2D and H-2K have been implicated (1-4) but a predominant role of H-2K in vaccinia viral infection (14) and of H-2D in other systems (11,(15)(16)(17)(18)(19) including tumor antigens (11) has been noted.…”
mentioning
confidence: 99%
“…Bevan (14) has shown that mouse cytotoxic T cells directed against minor alloantigens must share the same allele at either the H-2K or H-2D locus with the target cell. Similarly, several other investigators (15)(16)(17) have dem-nstrated an association between MHC antigens and tumor-specific transplantation antigens. Although the chemical basis for these molecular interactions is as yet unknown, it is not too surprising that a similar process may be mediated by/-region antigens on other MHC antigens.…”
Section: T-lymphocyte Activation Bymentioning
confidence: 78%
“…It is unlikely that histocompatibility antigens themselves are involved in the antigenic site, as has been suggested for TAAs in other systems (Germain, Dorf and Benacerraf, 1975;Schrader and Edelman, 1976) since 51Cr-labelled tumour target cells allogeneic to the NK cells are readily lysed (Zarling et al, 1975;Kiessling et al, 1975a) and unlabelled allogeneic tumour cells can also successfully compete in cellular competitive-inhibibition assays with 51Cr-labelled tumour cells (Zarling et al, 1975;Kiessling et al, 1975a). Since normal lymphoid cells do not inhibit in such assays it has been inferred that normal tissue antigens are not involved (Zarling et al, 1975).…”
mentioning
confidence: 93%
“…It is unlikely that histocompatibility antigens themselves are involved in the antigenic site, as has been suggested for TAAs in other systems (Germain, Dorf and Benacerraf, 1975;Schrader and Edelman, 1976) (Zarling et al, 1975;Kiessling et al, 1975a). Since normal lymphoid cells do not inhibit in such assays it has been inferred that normal tissue antigens are not involved (Zarling et al, 1975).…”
mentioning
confidence: 98%